2015
DOI: 10.1021/acssuschemeng.5b00965
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell Biocatalytic Processes with Ionic Liquids

Abstract: Whole-cell based biocatalysis in ionic liquids (ILs)-containing systems has attracted increasing interests in recent years. Compared to bioreactions catalyzed by isolated enzymes, the major advantages of using whole cell in biocatalytic processes are that cells provide a natural intracellular environment for the enzymes to function with cofactors regeneration in situ. An increasing number of renewable ILs are now accessible as a result of the ongoing progress in designing strategy of ILs and the sustainable en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 135 publications
0
52
0
Order By: Relevance
“…As multiple recent and comprehensive reviews on ionic liquids [32,33] and their application in whole cell catalysis [34,35] can be found, we would like to only highlight some particularly impressive publications.…”
Section: Ionic Liquids and Deep Eutectic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…As multiple recent and comprehensive reviews on ionic liquids [32,33] and their application in whole cell catalysis [34,35] can be found, we would like to only highlight some particularly impressive publications.…”
Section: Ionic Liquids and Deep Eutectic Solventsmentioning
confidence: 99%
“…Even though the compatibility was screened for living cells, and not with resting/dead cells in biotransformations, the results serve as a useful hint for IL selection. Good compatibility was generally found for imidazolium-based salts of short alkyl chain length, especially when they were mixed with alkyl sulfate anions [36], which might be another reason why these cations represent the most frequently used ILs in biocatalytic contexts in addition to their good commercial availability and wide application [35]. A trend of increasing catalyst activity with decreasing alkyl chain length described by Wood et al was confirmed in the stereoselective reduction of ethyl acetoacetate using immobilized Acetobacter cells in biphasic systems [37].…”
Section: Ionic Liquids and Deep Eutectic Solventsmentioning
confidence: 99%
“…1). 4,5 The attractive properties of ILs include ease of separation, recyclability, and immobilization on heterogenous solid supports, [6][7][8][9] and the combined advantages of environmentally friendly heterogeneous catalysis and sustainable catalytic properties of polymer supported ionic liquids (PSILs) have resulted in their being recognized as ranking among the best green catalytic systems. Furthermore, the heterogenization of active molecules to aid the isolation and separation of catalysts has resulted in many attempts to utilize PSILs in various organic transformations over the last two decades.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), as clean alternative environmentally friendly solvents to organic solvents, have been evaluated widely for performing whole cell catalytic reactions as potential media to overcome the limitations . ILs are capable of dissolving various polar and nonpolar compounds due to their unique properties, being non‐volatile, non‐flammable and highly stable .…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs), as clean alternative environmentally friendly solvents to organic solvents, have been evaluated widely for performing whole cell catalytic reactions as potential media to overcome the limitations. [13][14][15] ILs are capable of dissolving various polar and nonpolar compounds due to their unique properties, being non-volatile, non-flammable and highly stable. 16 Recently, biocatalytic reaction conducted in IL-containing systems has been extensively studied, and some valuable results were achieved in terms of the enantioselectivity and activity of biocatalysts.…”
Section: Introductionmentioning
confidence: 99%